A study on the financial viability of video retail industry in Iloilo City - Palomo, Yorelinda P.
To assess and analyze the business profitability of video retail industry in Iloilo City for what ever purpose it may later serve to prospective entrepreneurs in the future. To be able to determine the net returns on investment as expressed in percentage. The study covers only respondents located in various areas of Iloilo City. The question prepared were purposely addressed to customer's problems and needs in relation to the video retail industry. The research method used in this study is random sampling. Questioners were given out to 100 respondents on the personal basis to avoid delay in data collection. After data were gathered, tabulated and analyzed, accounting records were also collected. The sales report and expenditures were the contributing factors in the analysis of video retail business' profitability. the combination of accounting records and customers' demand and preferences make the researcher conclude that video retail industry is still profitable. It was found out that majority of the respondents patronize video house as a form of their entertainment, provided the location is conveniently accessible. The quality of tapes must be considered and the latest movie films should be updated. Action movie, would it be in English or Tagalog the demand is higher compared to drama and comedy. Survivability of this industry lies on the location of your establishment, the quality of tapes and latest title of your collection and the attitude of employees in dealing clients regardless of their status in the society. Thus, as an entrepreneurs, you must be sensitive to customers' likes and dislikes, if you wish to last in this endeavor.